2021
DOI: 10.5465/ambpp.2021.12506abstract
|View full text |Cite
|
Sign up to set email alerts
|

European Privacy Law and Global Markets for Data

Abstract: We demonstrate how privacy law interacts with competition and trade policy in the context of the European General Data Protection Regulation (GDPR). We follow more than 110,000 websites for 18 months to show that websites reduced their connections to web technology providers after the GDPR became effective, especially regarding requests involving personal data. This also holds for websites catering to non-EU audiences and therefore not bound by the GDPR. We further document an increase in market concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Binns & Bietti (2019) show how the market of online third-party trackers significantly increased its concentration over time (with Alphabet firms being present in more than 70% of the analysed sample). The same trend is observed by Batikas et al, (2020) in the web provider market.…”
Section: Discussion and Existing Evidencesupporting
confidence: 79%
See 1 more Smart Citation
“…Binns & Bietti (2019) show how the market of online third-party trackers significantly increased its concentration over time (with Alphabet firms being present in more than 70% of the analysed sample). The same trend is observed by Batikas et al, (2020) in the web provider market.…”
Section: Discussion and Existing Evidencesupporting
confidence: 79%
“…However, some recent empiric papers argue that soft privacy intervention could disproportionally harm smaller firms, increasing asymmetries in the market. Batikas et al, (2020) highlight this phenomenon in the market of web providers after implementing GDPR: the policy introduction lowered the market shares of all firms in favour of the market leader, Google. Garrett et al, (2022) also observed a similar result regarding web technology vendors (e.g.…”
Section: Discussion and Existing Evidencementioning
confidence: 98%
“…Campbell et al (2015) propose a model of how regulatory attempts to protect consumers' data privacy affect the structure of competition and find that the consent-based approach may disproportionately benefit firms that offer a larger scope of services, thus most adversely affecting small and new firms. This prediction has also been supported empirically in recent work on the EU GDPR (Batikas et al, 2020;Johnson et al, 2022). What has not been examined, however, is how such regulations affect the quality of the products and services offered by entrant firms.…”
Section: Relation To the Literaturementioning
confidence: 82%
“…4 The academic literature has been generally more critical. A number of empirical studies report adverse effects of the GDPR on businesses such as a decrease in the amount of data collected (Schmitt et al, 2021;Congiu et al, 2022;Aridor et al, forthcoming) which adversely affect AI startups and data-based innovation (Bessen et al, 2020;Batikas et al, 2023), dampened incentives to invest in technology ventures (Jia et al, 2021), a decrease in the number of mobile apps (Janßen et al, 2022), reduced website pageviews and e-commerce revenue (Goldberg et al, 2022), and increased market concentration in websites and web technology services (Schmitt et al, 2021;Peukert et al, 2022;Johnson et al, forthcoming). 5 In addition, several 1 Following the GDPR, many countries enacted similar privacy laws or amended existing ones in line with the GDPR.…”
Section: Introductionmentioning
confidence: 99%